An investigation of the talent development pathway in Scottish female football - Simpson, D.; Martindale, R. L. J.; Travlos, A.; Souglis, A.; Andronikos, G. (International Journal of Sport Psychology, 2022)
Literature in Talent Development (TD) for female sports is sparse and as- sumes applicability from existing male TD research. The purpose of this study was to gain an understanding of the TD pathway in Scottish female football. Five expert coaches and five international players were interviewed regarding their experiences within Scottish female football. Key findings demonstrated the main influences within the TD pathway. Mixed football was evident in the early stages while big gulfs were reported throughout the development process. Lack of capacity and re- sources to provide coherent support in a systematic way was the key constraint within the Scottish TD pathway. Practical implications include the education of club coaches and integration of sport psychologists in the development pathway.